Geological Mapping of Gunungbatu and Surrounding Areas, Bodeh District, Pemalang Regency, Central Java - Widiatmoko, Fajar Rizki; Aziz, Mochammad; Firmansyah, Irwan (Journal of Earth and Marine Technology (JEMT), 2021)
Mapping is the activity of collecting data from an area to be mapped, in the context of geology mapping means collecting data that includes descriptions of rocks, rock structures, rock positions, structure measurements (plunge/trend, pitch, microfold), rock thickness measurements, rock sampling and sketches. landscape, covering an area to be mapped. Research in the area of Gunungbatu and its surroundings, Bodeh District, Pemalang Regency, Central Java Province with the aim of knowing and knowing that it is in the research area by reconstructing the history of formation or geomorphological history, merely tectonic history in space and time, reconstructing geological history based on micropaleontological analysis. Based on the analysis carried out, it was found that the geomorphological units of the study area were divided into 5, namely the Gunungbatu Syncline Hills Unit, the Kali Bodas Anticline Valley Unit, the Girimulya Syncline Hills Unit, the Cenggiri Homocline Hills Unit and the Kebubung Homocline Valley Unit. The geology of the study area consists of two unofficial rock units in order from oldest to youngest, namely the claystone-sandstone unit and the sandstone-claystone unit. The geological structures of the pinpoint folds and faults are Mount Ketos Syncline, Kali Bodas Anticline, Gapura Syncline, Pertapan Igir Syncline, Cenggiri River Rising Fault, Kebubung Dextral Fault, and Girimulya Dextral Fault. The geological history of the research area begins with the book Unit of Claystone in the Middle Miocene Environment in Upper Bathyal. Furthermore, after the claystone-sandstone units were deposited, during the Middle Miocene – Late Miocene in the Deep Neritic Environment, the sandstone-claystone units were deposited with a turbidite mechanism. As well as the geological resource potential of the research area in the form of river utilization in the form of chunks of igneous rock, river sand deposits and gold seepage. Meanwhile, the potential for geological disasters in the form of landslides.